Reactivity of Deoxy- and Oxyferrous Dehaloperoxidase B from Amphitrite ornata: Identification of Compound II and its Ferrous-Hydroperoxide Precursor() - D’Antonio, Jennifer (2011)
Dehaloperoxidase (DHP) from the terebellid polychaete Amphitrite ornata is a bifunctional enzyme that possesses both hemoglobin and peroxidase activities. The bifunctional nature of DHP as a globin-peroxidase appears to be at odds with the traditional starting oxidation state for each individual activity. Namely, reversible oxygen-binding is only mediated via a ferrous heme in globins, and peroxidase activity is initiated from ferric centers and to the exclusion of the oxyferrous oxidation state from the peroxidase cycle. Thus, to address what appears to be a paradox, herein we report the details of our investigations into the DHP catalytic cycle when initiated from the deoxy- and oxyferrous states using biochemical assays, stopped-flow UV-visible and rapid-freeze-quench electron paramagnetic resonance spectroscopies, and anaerobic methods. We demonstrate the formation of Compound II directly from deoxyferrous DHP B upon its reaction with hydrogen peroxide, and show that this occurs both in the presence and absence of trihalophenol. Prior to Compound II formation, we have identified a new species which we have preliminarily attributed to a ferrous-hydroperoxide precursor that undergoes heterolysis to generate the aforementioned ferryl intermediate. Taken together, the results demonstrate that the oxyferrous state in DHP is a peroxidase competent starting species, and an updated catalytic cycle for DHP is proposed in which the ferric oxidation state is not an obligatory starting point for the peroxidase catalytic cycle of dehaloperoxidase. The data presented herein provide a link between the peroxidase and oxygen transport activities which furthers our understanding of how this bifunctional enzyme is able to unite its two inherent functions in one system.